(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Modified starches have gained popularity in recent years due to the availability of starch. Graft polymerization is one of the ways to improve the properties of starch. Starch was obtained by process of wet milling from four genotypes Cassava tubers (TMS 96/1632, TMS 98/0581, TMS 07/ 0593 and TMS 01/1371), assigned as A, B, C, and D, respectively, were grafted with PAM and synthesized by polymerization method. Potassium Persulfate (PPS) was used as an initiator with ethanol-water solution used to remove the homo-polymer acrylamide (PAM). The starch-grafted copolymer was characterized by Fourier transform infrared spectroscopy. From the result, it was observed that the FTIR spectra for the four starches grafted onto Polyacrylamide Monomer showed the presence of PS-g copolymer with new absorption bands at the range of 1644cm-1 1654cm-1 this indicates a primary amide group in the polyacrylamides. The drilling fluids treated with the PS-g copolymer showed mud weights between 8.6 9.0 with genotype D S-g-PA copolymer presenting a better rheology properties and fluid loss control. All drilling fluids prepared with copolymerized starch exhibit shear thinning and pseudoplastic properties.